Irrigation Sluice Control System Using Algorithm Based DC Motor PID And Omron PLC - Prastiyo, Duwi; Aji, Wahyu Sapto (Peneliti Teknologi Teknik Indonesia, 2023)
Automatic control system or control system (control system) is a system that aims to control a process so that the output produced can be controlled so that no errors occur. Automatic control in a system is very necessary because not all can be controlled by humans with precision, so it is necessary to have a control system that can monitor at the same time as the desired command execution. This research is to design a prototype irrigation sluice control system using a potentiometer, PID algorithm, PLC OMRON CP1E NA20DR-A and DC PG 28 motor as actuator. This research was conducted at the system design stage, both in hardware design and software design. The results of the tests that have been done show that the PID works well, this can be known from the state of the Output Word value